Success rate of immediate nonfunctional loaded single-tooth implants: Immediate versus delayed implantation - Ribeiro, Fernando Salimon; Pontes, Ana Emilia Farias; Marcantonio, Elcio; Piattelli, Adriano; Neto, Rodolfo Jorge Boeck; Marcantonio, Elcio [UNESP] (Lippincott Williams & Wilkins, 2008)
Purpose: The aim of this study was to evaluate the success rate of maxillary immediate nonfunctional single-tooth loaded implants used into fresh extraction sites (immediate placement condition) or healed ridge (delayed placement condition).Materials and Methods: Eighty-two dental implants were placed in the maxilla of 64 consecutive patients from Private practice office and from a specialization course in Implantology. Forty-six implants were inserted under immediate placement condition, and 36 were inserted under delayed placement condition. The criteria used to evaluate success rate were those previously described by Albrektsson and Zarb (Int J Prosthodont 1993;6: 95-105), and follow-up period ranged from 18.0 to 39.7 months.Results: Seventy-nine implants fulfilled the success rate criteria (96.3%). Moreover, differences concerning implantation condition were not significant (P = 0.33, Qui-square test): three of the failed implants were from immediate placement group (success rate of 93.5%), and none was from delayed placement group (success rate of 100.0%).Conclusion: In the present sample, no statistically significant differences were detected for immediate nonfunctional single-tooth loaded implants under immediate placement condition in comparison with those inserted under delayed placement condition; both protocols had high success rate in maxillary incisors, canines, and premolars areas.
Keywords: dental implants; immediate loading; immediate implantation; success rate; osseointegration